2005
DOI: 10.1007/s10006-005-0648-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurinom des harten Gaumens bei einem elfjährigen Mädchen

Abstract: An 11-year-old girl presented with a 3-month history of painless swelling of the hard palate. CT scan showed a right palatinal mass of 2 cm, reaching into the right maxillary sinus. After complete surgical excision the histological findings showed a neurinoma (Antoni type A). During a 2-year follow-up, there were no signs of recurrence. Because of the benign tumor type we considered the young patient to be healed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…S-100 staining was employed in all of the 27 amenable cases, and showed strong immunoreactivity in all of the employed cases. Other authors revealed varying degrees of positive immunoreactivity with different stains: vimentin, 15 19 42 epithelial membrane antigen (EMA), 24 49 SOX-10 (present case), neuron specific enolase (NSE), 15 glial fibrillary acidic protein (GFAP), 24 CD-56 and CD-57, 24 and CD-34 and CD-117. 49 Immunonegative results were noted with the following stains: actin, 21 neurofilament protein (NFP), 24 52 smooth muscle antigen, 37 cytokeratin, 46 AE1/AE3, 24 and Calponin.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…S-100 staining was employed in all of the 27 amenable cases, and showed strong immunoreactivity in all of the employed cases. Other authors revealed varying degrees of positive immunoreactivity with different stains: vimentin, 15 19 42 epithelial membrane antigen (EMA), 24 49 SOX-10 (present case), neuron specific enolase (NSE), 15 glial fibrillary acidic protein (GFAP), 24 CD-56 and CD-57, 24 and CD-34 and CD-117. 49 Immunonegative results were noted with the following stains: actin, 21 neurofilament protein (NFP), 24 52 smooth muscle antigen, 37 cytokeratin, 46 AE1/AE3, 24 and Calponin.…”
Section: Resultsmentioning
confidence: 61%
“…Partial/complete bony erosion was noted in 6 instances. 15 16 33 37 38 51 The lesion was seen eroding into the right maxillary sinus through the floor of the sinus in one case; 15 while in another patient, the mass was seen invading the nasal cavity through the palatal bone. 38 Orthopantomogramand maxillary occlusal radiography showed mostly a radiolucent lesion, without any bony alteration or periapical changes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,4,5 However, schwannomas that present in the oral cavity are relatively rare, constituting around 1% of all described cases in the head and neck region. 2,3,4 Here, we present a case of an intraoral schwannoma, in a thirteen year old boy.…”
Section: How To Cite This Articlementioning
confidence: 95%